A Digital Assessment of the Maxillary Deformity Correction in Infants With Bilateral Cleft Lip and Palate Using Computer-Aided Nasoalveolar Molding. Issue 6 (September 2017) - Gong, Xin; Zhao, Jun; Zheng, Jiawei; Yu, Quan
Abstract : Objectives: To evaluate the maxillary alveolar repositioning of the infants with bilateral cleft lip and palate (BCLP) undergoing computer-aided nasoalveolar molding (CAD-NAM). Methods: A total of 19 BCLP infants undergoing CAD-NAM were recruited as the treatment group, and 21 nonpresurgically treated BCLP patients served as controls. The upper alveolar morphology was measured and evaluated. Changes in all variables between pre- and post-CAD-NAM were compared. Results: By the end of CAD-NAM, significant difference was found in the P-A, P'-A', and L-ideal midline ( P < 0.01); in the sagittal dimensions, significant difference was found in the P-TT', P'-TT', I-TT', A-X, and A'-X' ( P < 0.01), while in the vertical dimensions, significant difference was found in the alveolus height in the bilateral canine regions ( P < 0.01). Conclusion: Computer-aided nasoalveolar molding can effectively reduce the cleft gap, correct the alveolar midline deviation, and retract the projection and outward rotation of the premaxilla segment, and normalize the contour of the alveolus.